Paolina's Innocence : Child Abuse in Casanova's Venice. - Wolff, Larry (Stanford University Press, 2012)
In the summer of 1785, in the city of Venice, a wealthy 60-year-old man was arrested and accused of a scandalous offense: having sexual relations with the 8-year-old daughter of an impoverished laundress. Although the sexual abuse of children was probably not uncommon in early modern Europe, it is largely undocumented, and the concept of "child abuse" did not yet exist. The case of Paolina Lozaro and Gaetano Franceschini came before Venice's unusual blasphemy tribunal, the Bestemmia, which heard testimony from an entire neighborhood-from the parish priest to the madam of the local brothel. Pao.